ANALYSIS OF SOCIAL CAPITAL IN ISLAMIC MICROFINANCE - Ahmad Ma'ruf; Widhia Restiawati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
This study aims to analyze the social capital in the form of trust, social networks, and norms in Islamic Microfinance, with case study in several BMTs in Yogyakarta. In this study, sample of respondents are selected using purposive sampling. This study used a qualitative method with descriptive statistical analysis. Based on the analysis, the result is BMT has succeeded a good record on doing the social capital and trust has the highest value compared to norms and social networks. Trust becomes the most social capital variables that is widely applied in BMT. While norms become the variable that have smallest value of social capital.